Analysis of Speech Act Theory in the News â€œIndonesia's Urge on Access to Education for Women in the Talibanâ€ on the Tempo.co page - Rizka Akmalia; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
This study aims to examine pragmatics in speech act theory in the news